The Development of PLC Management Model for Teachers Development of Learning Management through Active Learning Approach based on PAR : A Case Study of Tessaban 4 (Ban Ching Rai) School in Lampang Province - Rattanasirinichakun, Nat; Wilairat, Woraya (Journal of Modern Learning Development, 2022)
The objective of this research is aim 1) To study the conditions, problems, and needs 2) To create a model 3) To experiment with a model and 4) To Lessons Learned using a model of the PLC for teacher development in learning management through Active Learning approach with PAR. The research was conducted in 4 parts, the study of conditions, problems, needs, model experiments and reflective lessons from using the model. The group of informants consisted of 57 school administrators and teachers. Creative a model. The group of informants consisted of school administrators, teachers’ representatives, and experts, totaling 12 people with the data were analyzed using mean values, standard deviations, and content analysis. The results showed that: 1) A study of conditions, problems and needs was found that (1) The school administration focuses on participative management using the school base Management, PLC which are also new for teachers. (2) in terms of problem as some teachers still do not understand the PLC administration system (3) In terns of needs assessment as teachers want to encourage and support the development of knowledgeable learning management, environment conducive, organizing structuring facilitates Active Learning approach through PLC processes. 2) Creating a model was found that there were 7 main components which consisted of : (1) Principles (2) Inputs (3) Processes (4) Productivity (5) Positive impacts (6) Constructive data reintegration, and (7) Success factors. The overall evaluation of the suitability of the model was at a high level average. 3) Experimenting with the model was found that overall satisfaction assessment of the model was at a high level average. 4) Lesson transcripts of using model was found that the most suitable model for teacher development as participation in the exchange of learning and Active Learning approach.